White Tail Disease: A Viral Disease of Giant Freshwater Prawn, Macrobrachium rosenbergii (deMan) - pillai, Devika; C., Mohanakumaran Nair; Haridas, Divya V; P.M., Sherief (Fishery Technology, 2025)
Virus borne diseases are extremely difficult to control and constitute one of the major problems of prawn farming. Till recently, the giant freshwater prawn, Macrobrachium rosenbergii was regarded as disease resistant. But there have been recent reports on white tail disease (WTD), a virus borne disease of M.rosenbergii affecting the aquaculture industry of India. In this review, clinical signs, causative agents, mode of transmission and various diagnostic methods of white tail disease are discussed.